2013
DOI: 10.1027/1015-5759/a000134
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Revised Children’s Manifest Anxiety Scale in a Sample of Children and Adolescents from Poor Urban Communities in Cape Town

Abstract: The Revised Children’s Manifest Anxiety Scale (RCMAS) is regularly used with South African children, although its performance in this context has yet to be empirically evaluated. This study assessed the basic psychometric properties of the RCMAS using data collected in a large study examining the mental health of children and adolescents living in poor urban communities around Cape Town. Reliability of the full-scale was good, and the predicted relationships between anxiety, depression, PTSD, delinquency, age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 43 publications
1
35
1
Order By: Relevance
“…Fan and Sivo (2005) suggested that researchers should not solely rely on stand-alone indexes for assessing model fit. Additionally, the current study might provide the factor structure of anxiety symptoms in pediatric oncology population, and it may differ from previous studies in healthy children and adolescents (Boyes and Cluver, 2013;Pina et al, 2009;Reynolds and Richmond, 2008;Richmond et al, 1988;Wilson et al, 1990). This suggests that further structure evaluation of the RCMAS-2 in pediatric cancer population is clearly required.…”
Section: Discussioncontrasting
confidence: 65%
“…Fan and Sivo (2005) suggested that researchers should not solely rely on stand-alone indexes for assessing model fit. Additionally, the current study might provide the factor structure of anxiety symptoms in pediatric oncology population, and it may differ from previous studies in healthy children and adolescents (Boyes and Cluver, 2013;Pina et al, 2009;Reynolds and Richmond, 2008;Richmond et al, 1988;Wilson et al, 1990). This suggests that further structure evaluation of the RCMAS-2 in pediatric cancer population is clearly required.…”
Section: Discussioncontrasting
confidence: 65%
“…Total anxiety scores were calculated by summing all items. The RCMAS has been validated for use with South African samples (Boyes and Cluver 2013a) and the abbreviated version demonstrated excellent reliability in the current sample (Baseline: a = .81; Follow-up: a = .81).…”
Section: Anxiety Symptomsmentioning
confidence: 93%
“…Anxiety symptoms were measured using an abbreviated version of the widely used Revised Children's Manifest Anxiety Scale (Reynolds & Richmond, 1978). The full scale has been validated for use in South Africa (Boyes & Cluver, 2013). The 14 highest loading items from a factor analysis of the 2005 data were administered in 2009 (α = 0.82).…”
Section: Internalising Problemsmentioning
confidence: 99%